From burning to clean: how China’s heating transition reduces pollution and enhances land-use sustainability - Jiang, Xinyang (Frontiers in Environmental Science, 2025)
IntroductionAgricultural fires have posed significant challenges to environmental governance and the effective cultivation of land in China, prompting the government to implement the Clean Heating Policy (CHP) since 2013 as a key measure to reduce coal consumption and promote energy structure optimization. Moreover, growing land-use pressures—particularly those arising from agricultural intensification and rural energy demand—have further underscored the need for cleaner and more sustainable heating strategies.MethodsUsing county-level data on PM2.5 concentrations and agricultural fire frequencies, this paper employs a staggered Difference-in-Differences (DID) approach for empirical analysis.ResultsThe results indicate that the CHP significantly reduces PM2.5 concentrations by 4.8% and lowers agricultural fire occurrences by 17.4%, with the findings remaining robust. Further analysis demonstrates that the air pollution mitigation effect is primarily concentrated within a 50 km radius, while the fire suppression effect extends up to 100 km, especially pronounced in core grain-producing areas and non-resource-based cities.DiscussionOverall, this study highlights the positive role of the CHP in improving environmental quality, promoting more rational land resource use, and advancing sustainable energy transition.